Genotype identification of the Human Papilloma Virus in cervicouterine lesions carrier patients - Alexander Morales Fontaine; Odalys Rufina Peña Pérez; Alicia María Yabor Palomo; Vicente de Jesús Alvarez Yabor (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2016)
Background: during the last years there has been a high prevalence of women infected with genotypes of the human papilloma virus, considered as a high risk because of its high oncogenicity. Objective: to identify the genotypes of the human papilloma virus in cervical lesions carrier patients whose biopsies were analyzed in the pathologic anatomy department of “Dr. Ernesto Guevara de la Serna” General Teaching Hospital from January 2013, to December, 2014. Methods: a descriptive and cross-sectional study was carried out in 45 patients whose biopsies were taken at random from a total of 456 cases in which histopathological evidence of infection by the human papilloma virus was found, in the study period of time mentioned above. The biopsies were sent to the molecular biology laboratory of the virology department of ''Pedro Kourí” Tropical Medicine Institute in order to isolate and identify the types of this virus involved in the pathogenesis of the premalignant lesions studied. Secondary sources, given by the results of the identification of the genotype of the isolated virus sent from that institution, were used. Data were processed according to descriptive statistics, by means of percentage analysis. Results: in the 88,8 % of the sample, infection by the human papilloma virus was obtained, with high risk of oncogenicity, from which there was a predominance of genotype 16, with 26 cases (57,7 %), followed by 31, with 12 isolations (26,6 %), and 2 patients had genotype 52, for a 4,4 %. The 6,6 % of the sample was found to be infected with the genotype 11, which is considered to be of low risk, and in 2 cases it was not possible to type. Conclusions: there was a great predominance of patients affected by the human papilloma virus with a high risk of oncogenicity.